Crystallization Kinetics of Polyamide 2200 in the Modelling of Additive Manufacturing Processes by FE Analyses - BAJERSKI, Pawel; PĘCHERSKI, Ryszard Bolesław; CHUDY, Damian; JARECKI, Leszek (Engineering Transactions, 2019)
The thermoplastic polymers present amorphous or semi-crystalline structures which are very important factors in describing volumetric shrinkage. The thermoplastic materials are commonly used for production of daily life products, industrial or as the prototypes. Different techniques of manufacturing polymer structures are considered like: injection molding, extrusion, milling, additive manufacturing (AM). AM is a very fast developing field in the manufacturing and research. Unfortunately, components or prototypes made using the thermoplastic semi-crystalline materials in 3D techniques have quite low mechanical strength compared to the parts made by injection molding processes. It is caused by porosity obtained during the processing, as well as by fraction of crystallinity in the volume of the components. Additionally, the volumetric shrinkage is hard to predict without knowledge of its origin. Therefore, it is necessary to consider crystallization kinetics and the melting of the analysed materials. The investigations presented in this work concern the crystallization and melting model to be implemented in the finite element (FE) analyses. With use of the model, one can predict development of the structure during the real processes and, in the future, to control the warpage of the manufactured components.